2012
DOI: 10.4172/2157-7439.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Critical Process Parameters Evaluation of Modified Nanoprecipitation Method on Lomustine Nanoparticles and Cytostatic Activity Study on L132 Human Cancer Cell Line

Abstract: This work was focused on identification and evaluation of process parameters of modified nanoprecipitation method, for fabrication of lomustine nanoparticles, with the aim of reducing cancer cell viability at low concentration of lomustine. The parameters controlling particle size, mostly in nanosize, were solvent/nonsolvent composition and emulsification speed of homogenizer along with aqueous phase volume. This controlled particle size is below 250 nm. The stabilizer concentration controlled particle size is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(37 reference statements)
3
19
0
Order By: Relevance
“…Particle size, polydispersity index (PDI), zeta potential and scanning electron microscopy (SEM): The method used by Mehrotra and Pandit [10] was used. The Zetasizer used was of Malvern instruments, UK DTS Ver 5.10 and SEM was performed on Hitachi Japan S-3400N.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle size, polydispersity index (PDI), zeta potential and scanning electron microscopy (SEM): The method used by Mehrotra and Pandit [10] was used. The Zetasizer used was of Malvern instruments, UK DTS Ver 5.10 and SEM was performed on Hitachi Japan S-3400N.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…In-vitro drug release study: The method published by Mehrotra and Pandit [10] was used. Here all method is similar only lomustine was determined by dialysis method using Franz diffusion cell.…”
Section: Drug Content and Encapsulation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Mehrotra and Pandit 37 reported that high stirring rate enhanced mass transfer and rate of diffusion between the phases, which induced homogenous supersaturation and rapid nucleation to produce smaller sized microspheres. Thus, increasing homogenization speed decreased the size of the microsphere.…”
Section: Effect Of Surfactants On the F-lm Particle Sizementioning
confidence: 99%
“…To reduce the toxicity associated with high doses of lomustine, investigators have used nanoparticle technology to more efficiently deliver lower effective doses to the cellular target. 23,24 Numerous clinical trials have revolved around the use of lomustine or temozolomide in conjunction with additional therapeutic reagents, including, but not limited to, antibodies and pharmacological inhibitors. 2,43,45 Despite these attempts to markedly improve clinical outcomes, relatively few gains have been made in extending survival curves or drastically reducing the cytotoxicity associated with the use of these chemotherapeutic reagents.…”
mentioning
confidence: 99%